The relationship between intellectual capital and financial performance in Colombian listed banking entities (2021)
ABSTRACT: Purpose: This study aims to investigate the relationship between intellectual capital and the financial performance of 7 Colombian banks for the period 2010–2016. Design/methodology/approach: The information on the variables analysed was taken from each bank’s financial statement and the information on the market variables was obtained from the Colombian Stock Exchange. The value added intellectual coefficient method is used to identify whether there is a positive relationship with the following financial performance indicators: Return on assets (ROA), Market value (Market to book – MTB) and Tobin’s q (share value indicator). Intellectual capital efficiencies (human and structural capital) and capital employed have been analysed and their impact on financial performance has been measured through and econometric model. Conclusions: The analysis indicates that associations between , financial performance and corporate value are varied, so a homogeneous trend cannot be identified. Originality/value: This is one of the first research works in Colombia which analyses the incidence or impact of on financial and market performance of the banking sector in the long term.